15‐Hydroperoxy‐PGE2: Intermediate in Mammalian and Algal Prostaglandin Biosynthesis. Issue 49 (23rd October 2019) - Jagusch, Hans; Werner, Markus; Werz, Oliver; Pohnert, Georg
Abstract: Arachidonic‐acid‐derived prostaglandins (PGs), specifically PGE2, play a central role in inflammation and numerous immunological reactions. The enzymes of PGE2 biosynthesis are important pharmacological targets for anti‐inflammatory drugs. Besides mammals, certain edible marine algae possess a comprehensive repertoire of bioactive arachidonic‐acid‐derived oxylipins including PGs that may account for food poisoning. Described here is the analysis of PGE2 biosynthesis in the red macroalga Gracilaria vermiculophylla that led to the identification of 15‐hydroperoxy‐PGE2, a novel precursor of PGE2 and 15‐keto‐PGE2 . Interestingly, this novel precursor is also produced in human macrophages where it represents a key metabolite in an alternative biosynthetic PGE2 pathway in addition to the well‐established arachidonic acid‐PGG2 ‐PGH2 ‐PGE2 route. This alternative pathway of mammalian PGE2 biosynthesis may open novel opportunities to intervene with inflammation‐related diseases. Abstract : Inflamed : A new pathway to a long‐known lipid mediator, PGE2, was discovered in the red alga Gracilaria vermiculophylla (see Figure, top). Upon re‐investigation of the biosynthesis in macrophages, 15‐hydroperoxy‐PGE2 was also established as an intermediate in an alternative pathway in mammals.